Stock Market Development And Economic Growth: Evidence From Pakistan - MUHAMMAD KAMRAN; DR. MUHAMMAD ZAHID; SAID WALI; KAMRAN RIZWAN (Journal of Business & Tourism, 2021)
The key motive of this research is to explore the role of stock markets in economic growth in Pakistan for the span of 2000 to 2017 by using the Ordinary Least Square (OLS) and fully Modified Ordinary Least Square approach (FMOLS). The research explored the stock market development and economic growth association by employing the two significant measures of the stock market development, that is the size (DSIZE) and liquidity (DLIQ) of the market accompanied with Foreign Direct Investment (DFDI) and Stock Market Capitalization (DSMC). The outcomes reveal that the included independent variables have a positive effect on the dependent variable i. e. DGDP except for liquidity which has no significant effect on DGDP. It is expected that the findings of the investigation can be utilized by the government for destined follow-up and reassessment of economic development programs in Pakistan. The influential policy suggestion was the attraction of the Foreign Direct Investment and trade openness by exploring their major determinants and also focus on the positive relationship variables